Pelaksanaan Kewenangan Kejaksaan Negeri Denpasar dalam Penuntutan Tindak Pidana Narkotika oleh Anak - Komang Ayu Sintia Dewi; I Nyoman Putu Budiartha; I Nyoman Gede Sugiartha (Fakultas Hukum Universitas Warmadewa, 2020)
Abstract—Independent state power, especially the implementation of authority and duties in the field of prosecution is the duty of the Prosecutor as a government institution whose provisions are in accordance with Article 30 of the Republic of Indonesia Prosecutor's Law Number 16 of 2014. Handling of child crimes in conflict with the law regulated in the Criminal Justice System and different from adults are seen in quantity and quality in carrying out acts against the law, for example narcotics abuse. The formulation of the problem (1) how is the implementation of the authority of the Denpasar District Attorney in prosecuting child narcotics crimes? (2) what are the inhibiting factors for prosecuting children who commit criminal acts of narcotics at the Denpasar District Attorney's Office? The method used in this study is an empirical legal method. The results showed that it was synchronized between the regulations governing the prosecutor's authority in prosecution with the implementation of the prosecutor's authority in the Denpasar District Prosecutor's Office and the inhibiting factors of the Denpasar District Prosecutor's authority in prosecuting child narcotics crimes, namely infrastructure and facilities, awareness of the community and child in question. The countermeasures carried out by the Denpasar District Prosecutor's Office include the Greeting Prosecutor Program, School Entrance Prosecutors and the Wayan Adhyaksa application.